Biomineralization of endolithic microbes in rocks from the McMurdo Dry Valleys of Antarctica: implications for microbial fossil formation and their detection - Wierzchos, Jacek; García Sancho, Leopoldo; Ascaso, Carmen (Blackwell Publishing, 2005)
10 páges, and photos. In some zones of Antarctica’s cold and dry desert, the extinction of cryptoendolithic microorganisms leaves behind inorganic traces of microbial life. In this paper, we examine the transition from live microorganisms, through their decay, to microbial fossils using in situ microscopy (transmission electron microscopy, scanning electron microscopy in back-scattered electron mode) and microanalytical (energy dispersive X-ray spectroscopy) techniques. Our results demonstrate that, after their death, endolithic microorganisms inhabiting Commonwealth Glacier sandstone from the Antarctica McMurdo Dry Valleys become mineralized. In some cases, epicellular deposition of minerals and/ or simply filling up of empty moulds by minerals leads to the formation of cell-shaped structures that may be considered biomarkers. The continuous deposition of allochthonous clay minerals and sulfate-rich salts fills the sandstone pores. This process can give rise to microbial fossils with distinguishable cell wall structures. Often, fossilized cell interiors were of a different chemical composition to the mineralized cell walls. We propose that the microbial fossil formation observed was induced by mineral precipitation resulting from inorganic processes occurring after the death of cryptoendolithic microorganisms. Nevertheless, it must have been the organic template that provoked the diffusion of mineral elements and gave rise to their characteristic distribution pattern inside the fossilized cells. Peer reviewed